Repensar el "Mundo" Reflexiones y representaciones globales (siglos XV-XX) - Rinke, Stefan; Riojas, Carlos (Historamericana, 2022)
The book analyzes from different perspectives the imaginaries that result from the concept of the world as an independent element of reflection and representation from the 15th to the 20th century. It aims to help rethink the world based on a variety of connections and from a Latin American perspective.